New insights into the Upper Pleistocene archaeology of Northwestern Greece: The evidence from three open-air sites and its implication for Middle and Upper Palaeolithic hunter-gatherers’ activity and behaviour in Southeastern Europe - Ligkovanlis, S. (Journal of Greek Archaeology, 2017)
Northwestern Greece comprises one of the most important territories containing archaeological evidence on prehistoric hunter-gatherer activity in Southeastern Europe, having hosted, over the last fifty years, three generations of Palaeolithic researchers and also different schools of archaeological thought. This long-lasting activity, resulting in the identification and investigation of numerous sites yielding Palaeolithic finds, has in many cases created new methodologies of archaeological documentation and promoted the development of new ideas concerning both the material culture and its carriers.